To study the pattern of suspected adverse drug reactions in patients coming to the department of dermatology in Gauhati Medical College and Hospital, Guwahati, Assam, India - Borah, Ajoy; Lahkar, Mangala; Singha, Binita; Lihite, Ratan J.; Hazarika, Debeeka (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Cutaneous adverse drug reactions (ADRs) are the commonest ADRs (30-45%) and are responsible for about 2% of hospital admissions. This study was conducted to study the pattern of ADRs coming to the department of dermatology in a Tertiary Health Care Hospital. The objectives of the study were to assess the causality, severity, preventability, age distribution, sex distribution and the reactions occurring. Methods: Cross-sectional study. The suspected adverse drug reactions (ADRs) reported from the department of dermatology in the Spontaneous ADR reporting form was analysed in this study over a period of one year. Results: A total of 513 cases of reported ADRs were analysed. The highest number of ADRs was reported in the Age group 21-40 years with female preponderance. Erythematous maculopapular lesions were the most common ADR and maximum cases of ADRs were observed with steroids. Most cases were found to be probable (causality assessment), of mild severity and were probably preventable. Conclusions: The study showed that a number of drugs cause dermatological ADRs. These ADRs vary in their appearance, duration, causality, severity, and preventability.